The Importance of State Policy in Ensuring International Harmony and Religious Tolerance in Uzbekistan (Zien Journal of Social Sciences and Humanities, 2023)
This article provides information about the importance of state policy in ensuring inter-ethnic harmony and religious tolerance in Uzbekistan. Also, the measures implemented in our country for religious tolerance and inter-ethnic harmony are reflected in the article